DER DAN TATO TERHADAP LABA PERUSAHAAN - Pipit Mutiara; Deva Gustiana (Jurnal Financia : Akuntansi dan Keuangan, 2022)
ABSTRACT With good planning, management will work effectively and efficiently because the company's goal is to earn a profit, because the size of the profit achieved is a measure of the company's success. Parties such as company owners, investors, management, and creditors usually measure the company's success based on the company's ability as seen from the company's financial performance. One of the performance parameters is profit or profit. This study looks at the effect of DER and TATO on earnings changes. population used 5 companies. By using purposive sampling, the sample used is 4 companies. The research method used is descriptive and verification research methods with a quantitative approach. The data analysis method used is multiple linear regression analysis, classical assumption test and hypothesis testing. The results of this study indicate that DER does not have a significant effect on earnings changes, partially TATO has no significant effect on earnings changes, Simultaneously, DER and TATO have no significant effect on earnings changes. The results of the coefficient of determination test are 0.018, these results indicate that the large influence of DER and TATO on Profit Changes that can be explained by this equation model is 18% while the remaining 82% is influenced by variables outside the variables not examined.